Impact of supplementation of semen extender with antioxidants on quality of cooled or cryopreserved Marwari stallion spermatozoa - PRASHANT KUMAR; ASHOK KUMAR; J S MEHTA; G N PUROHIT; S K RAVI; YASH PAL; R A LEGHA; B N TRIPATHI; TR TALLURI (Indian Journal of Animal Sciences, 2021)
The aim of the present study was to evaluate the effects of supplementation of semen extender with two antioxidants namely Ascorbic acid (AA @ 0.9 g/L), Glutathione (GSH @ 2.5 mM), and combination of both (AA @ 0.9 g/L + GSH @ 2.5 mM) either in alone or in combination on the quality of cooled or cryopreserved Marwari stallion spermatozoa. For this purpose, a total of 24 ejaculates were collected from four adult and fertile Marwari stallions (6 ejaculates from each stallion) using an artificial vagina. Each freshly ejaculated semen sample was investigated for the semen quality parameters, viz. colour, consistency, total volume, gel volume, gel free volume, pH, progressive sperm motility, sperm concentration, sperm viability, sperm plasma membrane integrity, acrosomal integrity and DNA integrity. In the freshly ejaculated semen, no significant variation was found among individual stallions for various semen quality parameters except in sperm concentration. Pre-freeze and post-thaw semen evaluation revealed that the values for the most of the semen quality parameters were significantly higher in the semen extender being treated with the combination (AA @ 0.9 g/L +GSH @ 2.5 mM) of antioxidants group rather than AA and GSH alone or control. Addition of AA (0.9 g/L) and GSH (2.5 mM) to the freezing extender improved equine pre-freeze and post-thaw semen quality with the superiority of control group which indicates the beneficial role of supplementation of antioxidants to the stallion semen during cryopreservation process.